SV 2021
DOI: 10.22514/sv.2021.216
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II regulates TLR4/NF-κB signaling pathway to improve septic lung injury

Abstract: Sepsis is caused by the inadequate response to infection and may eventually lead to fatal organ dysfunction and a high mortality rate. Acute lung injury (ALI) caused by sepsis is an important cause of its high mortality, so effective treatment drugs are urgently needed. Icariside II (ICA II) is derived from Epimedii, a ubiquitous biological flavonoid compound. ICA II has shown multiple biological activities. ICA II alleviates LPS-induced neuroinflammation by inhibiting the TLR4 / MyD88 /NF-κB pathway, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Upon activation of NF-κB, degradation of IκB phosphorylation leads to phosphorylation of NF-κB p65 subunit and translocation from the cytoplasm to the nucleus to increase transcription of various inflammation-related genes, including TNF-α, IL-6, and other factors. 21,22 In order to further understand the antiinflammatory mechanism of PSTPIP2, we examined how it affected the NF-κB pathway. The results revealed that…”
Section: Competing Interestsmentioning
confidence: 99%
“…Upon activation of NF-κB, degradation of IκB phosphorylation leads to phosphorylation of NF-κB p65 subunit and translocation from the cytoplasm to the nucleus to increase transcription of various inflammation-related genes, including TNF-α, IL-6, and other factors. 21,22 In order to further understand the antiinflammatory mechanism of PSTPIP2, we examined how it affected the NF-κB pathway. The results revealed that…”
Section: Competing Interestsmentioning
confidence: 99%